Industrial Productivity and Growth Nexus in India: An Empirical Perspective - N.Karunakaran; Dr. Subhash. P. P (Journal of Advanced Research in Operational and Marketing Management, 2025)
Productivity serves as the fundamental catalyst for accelerating India’s developmental trajectory. Nevertheless, several structural and institutional challenges impede the nation’s capacity to rapidly elevate the living standards of its vast population to a desirable level. A sustained and significant enhancement in productivity would strengthen the competitiveness of India’s manufacturing sector by enabling it to achieve a more prominent position in international export markets. Improvements in productivity would further facilitate the country’s integration into global value chains and enhance its resilience against competitive pressures arising from imports that challenge domestic industries. Additionally, higher productivity is indispensable for improving the efficiency and competitiveness of small and medium-sized enterprises, particularly within the manufacturing domain. It would stimulate greater value addition across diverse economic activities, leading to increased profitability, which in turn would encourage higher levels of investment and result in better remuneration for workers. Collectively, these developments would accelerate economic expansion and foster greater prosperity among the Indian population.